The Effect of Use Various Lighting color on Productivity and Immunity Indicators in Broilers Chickens (Journal of Hama University, 2022)
A total of 240 one-day-old russ broilers were exposed to green light (GL), blue light (BL), white light (WL) and mix Green Blue light (GBL), respectively, by using a light-emitting diode system for 6 wk. There were for each light treatment 60 birds per pen. The effects of monochromatic light on Productivity Indicators and the immune response were studied. The results indicated that the feed conversion factor was the best for the GBL group, which recorded a value of 1.7, followed by the GL group with a value of 1.73, then BL with a value of 1.81 and finally WL with a value of 1.83. a good behavior and Calmness was also observed on birds exposed to green and blue colors and their mixture. As for the antibody titer for Newcastle disease, the highest immunoglobulin value was recorded in the GL group at the end of the experiment compared to the other groups with significant differences (P